2015
DOI: 10.1002/pon.3931
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical and mental health on relationship satisfaction: a dyadic, longitudinal examination of couples facing prostate cancer

Abstract: The effects of patient and spouse mental and physical health quality of life on their own as well as their partner's relationship satisfaction differed across time which will inform psychosocial interventions for couples with prostate cancer. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…This result is consistent with the literature ( Ross et al, 2016 ). Previous research has identified that marital status and relationship satisfaction are both protective factors of mortality and poor quality of life, including certain aspects of mental health among PCa survivors ( Bill-Axelson et al, 2013 ; Christie & Sharpley, 2014 ; Donovan et al, 2016 ; Eton & Lepore, 2002 ; Isbarn et al, 2010 ; Milonas et al, 2017 ; Occhipinto et al, 2019 ; Ross et al, 2016 ). To our knowledge, although important, there are no previous studies that have controlled for the presence or absence of current prescribed medication for anxiety, depression, or both, in studies examining mental health outcomes in this population.…”
Section: Discussionsupporting
confidence: 94%
“…This result is consistent with the literature ( Ross et al, 2016 ). Previous research has identified that marital status and relationship satisfaction are both protective factors of mortality and poor quality of life, including certain aspects of mental health among PCa survivors ( Bill-Axelson et al, 2013 ; Christie & Sharpley, 2014 ; Donovan et al, 2016 ; Eton & Lepore, 2002 ; Isbarn et al, 2010 ; Milonas et al, 2017 ; Occhipinto et al, 2019 ; Ross et al, 2016 ). To our knowledge, although important, there are no previous studies that have controlled for the presence or absence of current prescribed medication for anxiety, depression, or both, in studies examining mental health outcomes in this population.…”
Section: Discussionsupporting
confidence: 94%
“…However, couples potentially share not only PTG but also distress . In other words, while cancer survivors and their spouses could offer each other social support and emotional stability, they could also share negative outcomes, such as depression and anxiety . Therefore, research examining dyadic PTG that considers mutual dynamism and interdependence is required, but there is currently a lack of research concerning the corresponding topic.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has suggested that greater depressive symptoms predict lower marital satisfaction for both dyad members (Ross et al, 2016;Walker et al, 2013). Therefore, we included patients' and spouses' reports of depressive symptomatology as a covariate.…”
Section: Covariatesmentioning
confidence: 99%
“…This method provides a way for researchers to analyze dyadic data that are expected to be interdependent in nature by simultaneously estimating associations between one member's independent and dependent variable as well as the associations between one member's independent variable and the other dyad member's dependent variable. This modeling technique is especially useful for the current analyses as prior research has consistently shown a high correlation between partners' reports of marital satisfaction (Druley, Stephens, Martire, Ennis, & Wojno, ; Ross, Ranby, Wooldridge, Robertson, & Lipkus, ; Walker, Isherwood, Burton, Kitwe‐Magambo, & Luszcz, ).…”
Section: Introductionmentioning
confidence: 99%